Inhalation technique assessment and evaluation for the need of pharmaceutical intervention in respiratory pathologies patients - Paloma Castellano-Copa; Jaime Gulín-Dávila; Yveth Michelle Tajes-González (Farmacia Hospitalaria)
Objective: To evaluate rate and type of errors in inhalation technique of patients seen in hospitals at the observation area in the emergency department, as well as patients seen in the outpatients clinic at the primary care pharmaceutical consultation, and at the community pharmacy. Method: Descriptive observational study carried out by a hospital pharmacist, along with a primary care pharmacist and a community pharmacist. An anonymous survey was performed in order to collect different analyzed data. Each patient was asked to execute a complete demonstration on how they used their inhalers, to actively check the inhalation technique. Two checklists regarding the type of inhaler were established in order to assess said technique. Results were tabulated through Microsoft Excel® 2010 software and analyzed through R 3.5 statistical program. Results: A total of 66 patients (42 male, 24 female; mean age 67) were recruited. Out of all patients, 48.5% used more than one inhaler, which 34.4% used different types of inhaler, and 65.6% used different systems. A total of 39 patients were under dry powder inhaler therapy, and 38 were using pressurized metered dose inhalers. The most frequent errors –both in dry powder inhalers and pressurized metered dose inhalers–were: not performing a 10 second apnea and not slowly expelling air from the lungs. Around 50% of patients needed new learning after assessing their inhalation technique, even though 88.5% had already received previous training. Older aged patients performed a worse inhalation technique. Conclusions: There is a high rate of errors in the use of inhaled therapy, being even higher among older aged patients. The inhalation technique training by the medical staff seems inadequate, as it is crucial to raise awareness about the importance of health education for patients and their use of inhalers, to which a scheduled follow up and a technical and feedback obtained from the patient assessment is required.